1999
DOI: 10.1002/(sici)1097-0355(199921)20:1<42::aid-imhj4>3.3.co;2-2
|View full text |Cite
|
Sign up to set email alerts
|

Reactive attachment disorder in maltreated twins

Abstract: This case report summarizes in detail the clinical course of twins referred for intervention after maltreatment at 19 months of age who were followed to 36 months of age. Data from comprehensive assessment of parent-child relationships in these cases are reviewed and this material is considered in light of numerous family and systems factors that impacted the twins' clinical course. Diagnostic considerations pertaining to Reactive Attachment Disorder and the post-traumatic symptom of dissociation are presented… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
16
0
1

Year Published

2006
2006
2020
2020

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 14 publications
(20 citation statements)
references
References 0 publications
3
16
0
1
Order By: Relevance
“…However, if such a comparison would have revealed a link between ADS and SBS knowledge, it would still have been impossible to claim that insecure attachment is the core and most speci c issue that children with ASD struggle with, because theory suggests that the average child with any mental health problem will have less SBS knowledge than healthy controls [57]. This way, the current ndings resonate with other studies that failed to nd a link between ADS and insecure attachment [34] and with a mounting number of scholars argueing that insecure attachment is not the core and speci c issue characterizing attachment disorder symptoms [27,32,33,35].…”
Section: Discussionsupporting
confidence: 69%
See 1 more Smart Citation
“…However, if such a comparison would have revealed a link between ADS and SBS knowledge, it would still have been impossible to claim that insecure attachment is the core and most speci c issue that children with ASD struggle with, because theory suggests that the average child with any mental health problem will have less SBS knowledge than healthy controls [57]. This way, the current ndings resonate with other studies that failed to nd a link between ADS and insecure attachment [34] and with a mounting number of scholars argueing that insecure attachment is not the core and speci c issue characterizing attachment disorder symptoms [27,32,33,35].…”
Section: Discussionsupporting
confidence: 69%
“…Also, Rutter, Kreppner, and Sonuga-Barke reviewed empirical research on attachment disorders and concluded that ADS are indicative of emotional and behavioral dysregulation in general instead of attachment insecurity speci cally [33]. In a similar vein, other scholars argued that ADS might re ect not so much individual differences in attachment (in)security but re ect hyperarousal linked to post traumatic stress disorder or similar anxiety-related disorders [34,35,36]. Research further suggests that ADS and attachment have a different etiological background.…”
Section: Introductionmentioning
confidence: 99%
“…DSED shares the same etiology as RAD, that is, the child with the disorder must have experienced "insufficient caregiving" severe enough to explain the phenotype. Studies of children who have been maltreated 34,38,45,60,62 and those raised in institutions 9,42,51,52,63 have confirmed that indiscriminate behavior, the central feature of the phenotype, is increased compared to that in children who have not experienced such extremes of care.…”
Section: Etiology and Risk Factors For Dsedmentioning
confidence: 96%
“…In addition, comorbidity with depressive symptoms also has been noted in young children with histories of institutional rearing. 37 Some maltreated children have been documented to show signs of both posttraumatic stress disorder (PTSD) and RAD, 38 but no studies have yet documented the degree of comorbidity between RAD and PTSD. There is, however, longitudinal evidence that disorganized attachment in infancy is associated with the development of PTSD in schoolaged children who were exposed to significant traumatic events, 39 and children diagnosed with RAD are likely to have such trauma exposure.…”
Section: Comorbidity Of Radmentioning
confidence: 99%
See 1 more Smart Citation